Exploring the impact of the minimum pay scale and socio-demographic fac-tors on job satisfaction: An evidence from Ready-made garment workers in Bangladesh - Roy, Mritika; Zannat, Meheraz; Iqbal, Tareq; Chowdhury, Pritam; Ratna, Asia Jiasmin; Hossain, Md Arafat (Future Science / FSH-PH Publications, 2024)
Bangladesh's Ready-Made Garments contribute significantly to the country's economy and employment. In Bangladesh, spontaneous outbursts are usually caused by Ready-Made Garment workers due to inadequate pay, unpaid wages, and compensation for overtime work. Since these three criteria affect workers' job satisfaction, and some socio-demographic characteristics such as age, education, gender, marital status also influence job satiety, finally, all of these were needed to be studied in a single research study to narrate the impact of pay scale on garment workers, which had not done yet with the aid of nonparametric tests. So this research explored the impact of the 2018 revised minimum wage policy by examining workers' perceptions of wages, including basic pay, overtime compensation, various allowances (housing, medical, food, transportation), and the degree of workers' satisfaction within a group based on demographic traits. 80 responses, according to convenience sampling, were analyzed using descriptive statistics, the Mann-Whitney U and Kruskal-Wallis tests. The results highlighted dissatisfaction with basic pay, late payments, medical, and housing allowances but higher satisfaction with overtime compensation and transportation stipends. The study also found no significant difference in overall satisfaction with the wage structure based on gender or marital status, but it showed that aged, more educated workers are, for some reason, happier. Thus, the findings provide important insights for policymakers and industry stakeholders, shedding light on timely payment with a revised pay scale according to the present circumstances, considering worker needs like medical, housing allowances, etc. and creating an environment to involve women and young people.